A conceptual model of financial well-being for south african investors - Zandri Dickason Koekemoer; Suné Ferreira (Cogent Business & Management, 2019)
The satisfaction an individual experience with his or her financial position refers to financial well-being. Financial well-being can also be related to financial distress as its subjective indicator. The level of financial well-being may influence the financial decisions of investors and may vary according to their demographics. The aim of this study is to determine the level of financial well-being of investors and whether demographic variables play an influential role in investment decisions. The results from the study indicated that a significant difference exists between the financial well-being of male and female investors. Male investors were more likely to have an average or high financial well-being compared with female investors. A significant difference was also found between the financial well-being among different age categories. Older investors were more likely to have a low financial well-being compared to investors between the ages of 16 to 24.
Keywords: J11; G17; G24; 650; demographics; financial well-being; South Africa; investors